PENERAPAN ALGORITMA BOYER MOORE PADA APLIKASI FILOSOFER BERBASIS WEBSITE - Indra Jabinsan Sinaga; Ricky Crist G Imanta Kembaren; Dessy Milbina Br Bangun; Nasib Marbun (STMIK Budi Darma, 2019)
The philosopher is a scientist who is an expert in the field of philosophy or philosophy. A philosphere is generally able to think radically, rationally, competently, and have good logic. Filosofer has knowledge and extensive experience of science in the field of philosophy is something that can build a sense of optimism in general society, especially for students who are pursuing the field of philosophy to develop their knowledge related to philosophy, but a source of information that provides specifically for philosophers biographies are still limited so finding information is still difficult. Web application is one proof of current technological advances, web applications today can be utilized by many people and has become a necessity to access various kinds of important information. The philosophers web application built in this research is intended to make it easier for users to access information related to philosophers biographies that can have a positive impact on users. In the built-in web application philosophy is applied by Boyer Moore's algorithm. Keywords: Filosofer, Web, Algorithms, Boyer Moore.